Highly configurable low cost remote laboratory with integrated support for learning â?? Assessment of acquisition equipment - Samuelsen, Dag A. H.; Graven, Olaf H. (International Journal of Online and Biomedical Engineering (iJOE), 2013)
One of the activities when designing a remote laboratory is the action of selecting the data acquisition system. The hardware solutions available range from companies created high-quality components to self-designed solutions using discreet components in order to reduce the cost and gain full control over the specifications for the solution chosen. In the last few years the option of using open source, low-cost microcontroller board layouts based on microcontrollers have become available. The topic of this paper is the assessment of the quality of the data acquisition solution made available by the use of the internal analogue to digital converters (ADCs) of such low-cost solutions. The quality of the hardware is analyzed both in terms of measurement errors obtained through experimentation and comparison of quantitative data from the datasheets. The analysis presented serve as a basis for assessing whether the low-cost solutions are sufficient for running some or most of the remote laboratories, or if the increased cost of the budget solutions from professional acquisition modules can be defended.